Classical mechanics - Gupta, S. L.; Kumar, V.; Sharma, H. V. (Meerut: Pragati Prakashan, 2012)
In Classical Mechanics the concepts and theories of classical physics have been described in a way such as to cover an extensive field of physical phenomena. Laws of Mechanics have been applied to a variety of systems-atomic and electromagnetic etc. Problems from various university and competitive examinations have been worked out to aid in the understanding of the underlying theory and grasping its intricacies. subject matter is quite simplified and can be followed easily with the help of illustrations and solved problems. The book Completely covers the prescribed course of classical mechanics of all Indian Universities.
Includes bibliographical references.; Index 381-382p.
Keywords: Classical mechanics; Mechanics; Physics